Perbedaan Kualitas Hidup Pada Pasien Retinopati Diabetik Non-Proliferatif Berat dan Retinopati Diabetik Proliferatif di Poliklinik Vitreoretina Instalasi Rawat Jalan Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung - Nurhayati, Melan; Nur Amalia, Irma; ., Hafsa (Sehat MasadaJurnal, 2019)
Diabetic retinopathy (RD) is a specific microvascular complication of Diabetes Mellitus (DM) that causes visual impairement. Visual impairment that occurs in DR patients can affect the quality of life related to eye health. The latest data about DR patients from National Eye Center (NEC) Cicendo Eye Hospital Bandung was 2035 patients with Severe Non-proliferative Diabetic Retinopathy (Severe NPDR) and Proliferative Diabetic Retinopathy (PDR) are the most happened. The purpose of this study was to determine quality of life differences in patients with severe NPDR and PDR at the Vitreoretina Polyclinic Outpatient Departement NEC Cicendo Eye Hospital Bandung. This Research is a quantitative non-experimental with a comparative descriptive design. The sample was divided into two groups, they are Severe NPDR and PDR group, with 30 respondents each. The instrument that used in this study is the National Eye Institute Visual Function Questionaire-25 (NEI VFQ-25). Data analized by Chi Square test. The results showed that no differences in qualityof life in patients with severe NPDR and PDR in the Vitreoretina Polyclinic Outpatient Departement NEC Cicendo Eye Hospital Bandung (p = 1,000). This study illustrates the importance of providing education and encouragement to the patients with Severe NPDR and PDR for regular control about their visual impairment and their diabetes, so the patients will spared from decressing in their quality of life.